DETEKSI POLICY-MIX FIVE EMERGING MARKET DALAM MENENTUKAN FUNDAMENTAL EKONOMI - Tarisya Alfadhilla; Dewi Mahrani Rangkuty (JURNAL ILMIAH EDUNOMIKA, 2024)
This research aims to detect the policy mix of five emerging markets in determining economic fundamentals—mechanisms of monetary policy, fiscal policy, and macroprudential policy in the economy. The SVAR (structural vector autoregression) model shows that inflation, interest rates, and tax revenues influence gross domestic product in the short and long term. Inflation shows positive results on interest rates and negative results on tax revenues and the balance of payments. At the same time, government spending has a positive effect on tax revenues, interest rates, and gross domestic product. The balance of payments also affects gross domestic product. Monetary policy, fiscal policy, and macroprudential policy have a mutually influential relationship to maintain economic fundamentals.